Broodiness Trait of Chicken Through Molecular Investigation - Sartika, Tike (Indonesian Animal Sciences Society, 2005)
Incubation behavior of Kampung chicken is associated with the cessation of egg laying, and intensity of broodiness trait depends on genetic and environmental factors such as breed, management system, type of cages and photo periodicity. In this review, broodiness trait was investigated through molecular analysis. The result of the study concluded that there are two hypothesis of genetic incubation behavior. Some authors agreed that the incubation behavior is controlled by a major gene sexlinked on the Z chromosome. The prolactin receptor (PRLR) gene is a candidate gene for broodiness trait on the Z chromosome. However, the expression of broodiness in White Leghorn and Bantam hens cannot be explained by differences in the amounts of PRLR mRNA in the transcription or gross structure of the PRLR gene. The other hypothesis concluded that the incubation behavior is controlled by a small number of dominant autosomal genes with no sex linkage. Prolactin promoter (PRLp) gene is the major gene autosomal as starting point to express prolactin gene on the 2 chromosome. Prolactin promoter gene could be represented by the broodiness bands. Genotype AA and AC is identified as the broody genotype and BB as the non broody genotype. Key words: Broodiness, prolactin receptor, prolactin promoter, Kampung chicken